Dream content analytic scale for measuring studies-related topics: reliability and validity - Schredl, Michael (International journal of dream research, 2025)
According to the continuity hypothesis of dreaming, one would expect that students’ dreams quite often include studies-related topics as students spent a lot of time during the day visiting lectures, studying and other activities. The present paper describes the development of a reliable and valid scale for measuring studies-related topics in dreams. By analyzing a long dream series, it could be shown that the percentage of studies-related dreams significantly decreased after graduation; even though these topics remain quite common. Studying dreams with studies-related topics can help to learn more about the continuity between waking and dreaming, for example, the effect of stress levels on dream emotions.